Vpliv sodelovalnega gospodarstva na stanovanjsko pravo držav članic EU - Vlahek, Ana (Podjetje in delo, 2018)
Digital short-term rental platforms made it very easy for owners to rent out their premises for the purpose of tourist accommodation. Many individuals rent out their residential premises through digital platforms as their complementary economic activity, while relying on the rules of housing legislation that were not designed for the purpose of providing tourist accommodation but to regulate long-term rental housing relations. When renting apartments to tourists, they do not take into account the more stringent legal requirements for performing an economic activity in an apartment. Widespread short-term rental of apartments can be disturbing for regular residents in apartment buildings and can have a negative impact on the housing rental market. Consequently, some countries and cities have started regulating and limiting short-term tourist rentals. The purpose of the article is to outline the conditions for short-term rentals of residential premises according to the current Slovenian legislation, and the approach of digital platforms to ensure compliance with these conditions, as well as to determine where the current rules are inadequate and how they could be improved.
Keywords: Airbnb; etažna lastnina; gospodarstvo; gostinska dejavnost; kratkoročni najem stanovanja; omejitve kratkoročnega stanovanjskega najema; platforma za najem bivalne enote; sodelovalno gospodarstvo; stanovanjsko pravo